Visual Anthropology and the Collaborative Process with Incarcerated Women in the Photographic Diptychs Antropología de la mula by Adriana Bustos - Cuvardic García, Dorde (2026)
Introduction: The four photographic diptychs of Antropología de la mula, by the Argentinian artist Adriana Bustos, offer a dialectical representation of female drug carriers. Objective: As a result of an artistic intervention practice in a prison, this paper analyzes the representation —in Antropología de la mula— of the contrast between prison reality and the expectations of four women who participated in international drug trafficking. Methods: The theoretical framework used for this analysis is based on a Visual Feminist Anthropology approach. The portfolio studied is the product of a collaborative process between a group of incarcerated women and Bustos. Both actors establish a counter-hegemonic narrative, analyzed through autoethnography. Results: The diptychs stage the dehumanization of the female drug carrier visualizing her as a mule, an animal which acquires the allegorical meaning of the exploitation of human beings by the drug trafficking economy. Conclusions: The ‘mule’ represents the contemporary version of a series of subaltern subjects whose bodies have been disciplined by capitalist postmodernity, thus turning them into ‘pack animals’, participants, as well as victims, of international drug trafficking.